Electronic Structure and Slow Magnetic Relaxation of Low-Coordinate Cyclic Alkyl(amino) Carbene Stabilized Iron(I) Complexes - Samuel, Prinson P; Mondal, Kartik Chandra; Amin Sk, Nurul; Roesky, Herbert W; Carl, Elena; Neufeld, Roman; Stalke, Dietmar; Demeshko, Serhiy; Meyer, Franc; Ungur, Liviu; Chibotaru, Liviu F; Christian, Jonathan; et al. (Journal of the American Chemical Society, 2014)
Cyclic alkyl(amino) carbene stabilized two- and three-coordinate Fe(I) complexes, (cAAC)2FeCl (2) and [(cAAC)2Fe][B(C6F5)4] (3), respectively, were prepared and thoroughly studied by a bouquet of analytical techniques as well as theoretical calculations. Magnetic susceptibility and Mössbauer spectroscopy reveal the +1 oxidation state and S = 3/2 spin ground state of iron in both compounds. 2 and 3 show slow magnetic relaxation typical for single molecule magnets under an applied direct current magnetic field. The high-frequency EPR measurements confirm the S = 3/2 ground state with a large, positive zero-field splitting (∼20.4 cm–1) and reveal easy plane anisotropy for compound 2. CASSCF/CASPT2/RASSI-SO ab initio calculations using the MOLCAS program package support the experimental results.